Ethical explications of "visual turn" in contemporary culture - O. B. Shynkarenko (Ukrainian Cultural Studies, 2020)
The article is devoted to the coverage of possible ethical conclusions from the stated "visual turn" in the study of contemporary transformations of culture. The rapid growth of digital technological capabilities, which began at the end of the twentieth century and intensified in recent decades, has been characterized by changes in the nature and role of visualization in the socio-cultural space of the present. The socio- cultural effects of the reversal of cultural practice on the dominance of the visual component cause the urgent need to integrate ethical research into the scientific discourse on visualization, visual image, visual perception, and their influence on the state of human readiness for new behavioral requests and social relationships. Among the multi-sectoral discussions, "visual ethics" also took its place. However, the ethical aspect here is more related to the problems of regulating the relations that arise in the process of visual production (photojournalism, visual communication in the media, advertising content, etc.). It is considered in a certain applied aspect – as moral aspects of the relations of subjects and visual communication in the process of production and consumption of visual products. At the same time, visual studies tend to analyze imagistic representations while ignoring many of the ethical dimensions involved. The study of sociocultural practice, which has radically returned to the visual as its dominant characteristic and yet burdened by the dominance of new technologies of mediation by the loss of the directness of human contact, atomization, require a broader anthropological understanding of the formation of man as an active social actor. Such a task is seen in addressing the problem of a new reading of the problem of the correlation of ethos and aesthesis. For the "visual turn" as a trend of modern cultural studies, ethical orientation is seen in the trend of subject design of visual ethics as one of the areas of visual research.